1984
DOI: 10.1016/0014-5793(84)80923-0
|View full text |Cite
|
Sign up to set email alerts
|

The roles of intrinsic kinase and of kinase/activator protein in the enhanced phosphorylation of pyruvate dehydrogenase complex in starvation

Abstract: Extracts of heart mitochondria from fed and from 48 h starved rats subjected to gel filtration on Sephacryl S-300 gave 4 major protein peaks. Pyruvate dehydrogenase complex eluted in the void volume and was assayed for intrinsic pyruvate dehydrogenase kinase activity which was increased approximately 3-fold by 48 h starvation of the rat. A second fraction, containing peaks 2 and 3 which overlapped, enhanced the activity of the intrinsic kinase and corresponds to ~n~/activator protein described previously. Its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
1
1

Year Published

1986
1986
2007
2007

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 12 publications
3
35
1
1
Order By: Relevance
“…Nevertheless, different tissues may contain different ratios of kinase to complex and/or kinase to phosphatase, and these ratios may be markedly different in chow-fed-rat liver and in low-protein-diet-fed-rat liver. A substantial increase in the amount of pyruvate dehydrogenase kinase appears to be an important factor in starvation-induced inactivation of the pyruvate dehydrogenase complex (Kerbey et al, 1984). It is also possible that the 'activator protein', described by Fatania et al (1982) and shown to correspond to E1 of the complex by Yeaman et al (1984), plays some role in 'buffering' covalent modification of branched-chain 2-oxo acid dehydrogenase in liver of well-fed rats.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, different tissues may contain different ratios of kinase to complex and/or kinase to phosphatase, and these ratios may be markedly different in chow-fed-rat liver and in low-protein-diet-fed-rat liver. A substantial increase in the amount of pyruvate dehydrogenase kinase appears to be an important factor in starvation-induced inactivation of the pyruvate dehydrogenase complex (Kerbey et al, 1984). It is also possible that the 'activator protein', described by Fatania et al (1982) and shown to correspond to E1 of the complex by Yeaman et al (1984), plays some role in 'buffering' covalent modification of branched-chain 2-oxo acid dehydrogenase in liver of well-fed rats.…”
Section: Resultsmentioning
confidence: 99%
“…Kinasecatalyzed inactivation of PDC plays a key role in limiting glucose oxidation when more abundant fatty acids are used to provide oxidative energy (2). This routinely occurs in many tissues but is particularly important during starvation (2,(13)(14)(15)(16)(17)(18), when limited glucose must be conserved for glucose-utilizing tissues such as brain. PDC is similarly down-regulated due to high PDK activity in the diabetic state (2,(15)(16)(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…PDH kinase activities in ex- tracts of mitochondria from hearts of 24 h-starved virgin rats were 2.0-fold higher than in extracts of mitochondria from hearts of ad libitum-fed virgin rats (Table I). Previous studies have demonstrated a 2 to 4-fold increase in cardiac PDH kinase activities after 48 h starvation in male rats [40]. Starvation for 24 h was associated with 2.0-fold increase in cardiac PDH kinase activities in late-pregnant rats (Table I).…”
Section: Cardiac Pdh Activities In the Ad Libitum-fed State In Late mentioning
confidence: 91%